Chapter 2 The Sands of Abjection in The Sheltering Sky - Hentzi, Gary (Taylor & Francis, 2023)
The earliest novel in the group, The Sheltering Sky, is also the richest example of how the postwar counterculture absorbed influences from French culture, a significant source of inspiration for these writers, although Bernardo Bertolucci's film adaptation foregrounds only one such influence, offering a visual language derived from the novel's existentialist surface narrative while revising the encounter with the cultural other in an effort to make it palatable to the sensibilities of a later age. The main task of the chapter is therefore to recover the novel's surrealist dimension, an aspect of the book that has never been fully expounded. This concealed dimension takes the form of a poetic imagery that stages a dialectic of purity and abjection, a destabilizing counter-narrative that the chapter analyzes with the help of ethnographic and psychological parallels.